Choices, affects and trans representation: An analysis of mechanics and gameplay in Tell Me Why - Marak, Katarzyna; Strehlau, Nelly (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article discusses selected aspects of the 2020 game Tell Me Why, focusing on particular gameplay mechanics pertaining to player choices and the manner in which they influence player emotions, as well as on the representation of trans experience in the game. The authors draw both on affect theory and on approaches derived from game studies concerning the presence of emotions in gameplay. In the final part of the text, trans representation in Tell Me Why is analysed and juxtaposed with the readings typically found in the game’s reviews.